PENGARUH LEVERAGE, LIKUIDITAS, FIRM SIZE DAN CAPITAL EXPENDITURE TERHADAP CASH HOLDING PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Santioso, Linda; Daryatno, Andreas Bambang (Ultima Management : Jurnal Ilmu Manajemen, 2023)
Abstract - Cash holding or commonly referred to as cash and cash equivalents owned by the Company which is used to finance operational activities such as purchasing raw materials or merchandise, purchasing capital goods, paying salaries or wages, paying off debt obligations, paying dividends and other transactions required by the company. Cash Holding plays a very important role in determining whether a company is healthy or not, often associated with ownership as the dependent variable. The aim of this research is to obtain empirical evidence regarding the influence of leverage, liquidity, company size and cost of capital on cash flow in real estate and real estate companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2021. Technical sampling used in this research was a purposive sampling technique. Data processing uses the Eviews 13 program. The research results show that the independent variable Leverage has a negative and significant influence on Cash Holding where hypothesis 2 is not rejected, Liquidity has a positive and significant influence on Cash Holding where hypothesis 2 is not rejected, Firm Size has a positive influence but not significant on Cash Holding where hypothesis 3 is rejected, and Capital Expenditure has a positive and significant influence on Cash Holding where hypothesis is rejected. From the empirical evidence above, the implication obtained in this research is that companies that have high leverage need sufficient reserve funds to avoid financial distress, so that the company's activities can run smoothly. In order to cover short-term financing needs, companies really need good liquidity, meaning there is sufficient reserve funds. The bigger a company, the bigger the transactions will be too. Here it is necessary to have reserve funds to be used to meet financing needs so that the company's operations are not disrupted. Capital expenditures made by a company in making investments should use internal funds so that they do not add additional burden. If capital expenditure uses external financing or debt, it will reduce the Company's liquidity level because it has to pay interest or other expenses. Keywords: Capital Expenditure; Cash Holding; Firm Size; Leverage; Liquidity